Probe-based label-free SERS for identification of breast cancer-induced serum metabolic profiles in patients - WANG Meng, SHEN Xuejing, LIU Jia, SHANG Lulu, ZHANG Mo (Jichu yixue yu linchuang, 2025)
Objective To detect Serum metabolites with label-free surface-enhanced Raman spectroscopy (SERS) for quickly distinguishing the metabolic profiles of breast cancer patients and healthy subjects. Methods A kind of Plasma nano-material was synthesized as a probe for SERS, which has also been used to detect Raman reporter molecules to assess its detection capability. Serum samples from breast cancer patients and healthy subjects were collected and the proteins were precipitated with methanol and removed to collect serum metabolites. Probe-based SERS was used to analyze the serum metabolites of patients and explore the changes in the metabolic profiles of breast cancer patients. Results The SERS probe was synthesized and validated. An analytical method based on SERS probe was established, which achieved a linear range (LR) of 4 orders of magnitude and a limit of detection (LOD) up to 10 nmol/L. Raman spectra of serum metabolites from 5 breast cancer patients and 5 healthy subjects were analyzed to study differences in metabolite changes. Conclusions In this study, the molecular spectrum differences of serum metabolites in breast cancer patients were screened by probe-based SERS method, which provides a technology support research on the metabolic changes caused by breast cancer so potentially provide a new method for fast breast cancer screening.